2012
DOI: 10.1021/jm300253q
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Nucleic Acid–Aminosugar Conjugate Targeting Transactivation Response Element of HIV-1 RNA Genome Shows a High Bioavailability in Human Cells and Strongly Inhibits Tat-Mediated Transactivation of HIV-1 Transcription

Abstract: The 6-aminoglucosamine ring of the aminoglycoside antibiotic neomycin B (ring II) was conjugated to a 16 mer peptide nucleic acid (PNA) targeting HIV-1 TAR RNA. For this purpose we prepared the aminoglucosamine monomer 15 and attached it to the protected PNA prior to its cleavage from the solid support. We found that the resulting PNA-aminoglucosamine conjugate is stable under acidic condition, efficiently taken up by the human cells and fairly distributed in both cytosol and nucleus without endosomal entrapme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 93 publications
2
34
0
Order By: Relevance
“…The cellular uptake of naked PNA is negligible. Earlier, we showed that PNA conjugated with neamine or glucosamine is efficiently taken up by the cells without endosomal entrapment (15,20) . We conjugated 15-mer biotinylated PNAs with neamine at the N terminus and with biotin at the C terminus via a Lys residue (Fig.…”
Section: Sequence Specificity Of Pna-neamine Conjugate Targeted To Comentioning
confidence: 97%
“…The cellular uptake of naked PNA is negligible. Earlier, we showed that PNA conjugated with neamine or glucosamine is efficiently taken up by the cells without endosomal entrapment (15,20) . We conjugated 15-mer biotinylated PNAs with neamine at the N terminus and with biotin at the C terminus via a Lys residue (Fig.…”
Section: Sequence Specificity Of Pna-neamine Conjugate Targeted To Comentioning
confidence: 97%
“…More recently, in T-cell lymphocytes, the conjugation of aminoglucosamine to a peptide nucleic acid (PNA) targeting HIV-1 TAR significantly improved the cellular uptake of the PNA (Das et al, 2012). In addition, the amino sugar conjugate reduced luciferase activity greater than naked PNA and scrambled PNA conjugate controls.…”
Section: Targeted Conjugatesmentioning
confidence: 99%
“…The conjugation of amino sugars to an aglycone improves the basicity [35], alters the pharmacological properties [2,36,37], and also alters the mechanism of action of parent compound [38,39]. Moreover, the inherent positive charge of the amino sugar also enhances the solubility and potential for ionic interactions under normal physiological conditions [40,41].…”
Section: Discussionmentioning
confidence: 99%